MATHEMATICAL MODELING OF OMIC PROPULSION SYSTEM IN MICROSATELLITE GROUP FORMING - Андрей Владимирович Погудин (Авіаційно-космічна техніка та технологія, 2018)
The subject of the study in the article is the mathematical model of the propulsion system. It is built on the basis of the formed transfer functions of the elements. The goal is to rationalize the process of heating the onboard propulsion system on the basis of mathematical model under given constraints. Tasks: formalization of processes in an electric heating engine with a working body ammonia; formalization of the model of the onboard propulsion system; formation of the structural scheme; consideration of physical processes occurring in the nodes of the propulsion system; description of gas and hydraulic processes; the description of thermodynamic and electrokinetic processes; The construction of a mathematical model based on transfer functions. The methods used are: models of transfer functions of a tank, a filter, a steam generator, a receiver and a jet, an engine with their ranges of work. The following results are obtained. A block diagram of the onboard propulsion system was added, supplemented with a control unit and a power supply system. A formalized mathematical model of an onboard propulsion system with working body ammonia is created. From it formed a model consisting of the key elements that make up the onboard propulsion system, which is used when rationalizing the heating of the working fluid. The scientific novelty of the results is as follows. The mathematical model of the electro-heating propulsion system onboard small space vehicles has been further developed through its application to calculate the traction characteristics of the dispenser, which makes it possible to use an ammonia electric heating rocket engine in the formation of a constellation of satellites. The limitations of the operating parameters of the model are introduced. It was proposed to conduct the further workability of the model in Matlab Simulink. Thus, a rational value of the current and voltage parameters will be obtained, at which the time of the system's output to the operating mode will be minimal, and the thrust is maximum for the given operating temperature and pressure ranges